2007
DOI: 10.1091/mbc.e06-08-0707
|View full text |Cite
|
Sign up to set email alerts
|

Two Mammalian Sec16 Homologues Have Nonredundant Functions in Endoplasmic Reticulum (ER) Export and Transitional ER Organization

Abstract: Budding yeast Sec16 is a large peripheral endoplasmic reticulum (ER) membrane protein that functions in generating COPII transport vesicles and in clustering COPII components at transitional ER (tER) sites. Sec16 interacts with multiple COPII components. Although the COPII assembly pathway is evolutionarily conserved, Sec16 homologues have not been described in higher eukaryotes. Here, we show that mammalian cells contain two distinct Sec16 homologues: a large protein that we term Sec16L and a smaller protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
242
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(268 citation statements)
references
References 46 publications
22
242
2
2
Order By: Relevance
“…The SEC16B encodes long (Sec16L) and short (Sec16S) proteins, which are expressed ubiquitously in various tissues. 25 Sec16L and Sec16S are required for secretory cargo traffic from the endoplasmic reticulum to the Golgi apparatus. 25,26 We have reported that SCG3 and secretogranin II (SCG2) form secretory granules with orexin, neuropeptide Y (NPY) and proopiomelanocortin (POMC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEC16B encodes long (Sec16L) and short (Sec16S) proteins, which are expressed ubiquitously in various tissues. 25 Sec16L and Sec16S are required for secretory cargo traffic from the endoplasmic reticulum to the Golgi apparatus. 25,26 We have reported that SCG3 and secretogranin II (SCG2) form secretory granules with orexin, neuropeptide Y (NPY) and proopiomelanocortin (POMC).…”
Section: Discussionmentioning
confidence: 99%
“…25 Sec16L and Sec16S are required for secretory cargo traffic from the endoplasmic reticulum to the Golgi apparatus. 25,26 We have reported that SCG3 and secretogranin II (SCG2) form secretory granules with orexin, neuropeptide Y (NPY) and proopiomelanocortin (POMC). 6,27 Thus, Sec16 may have a role in the transport of SCG3 and SCG2 together with orexin, NPY and POMC from the endoplasmic reticulum to the Golgi apparatus, and also in regulating the secretion of these appetiterelated peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Of the new HSP105-interacting proteins that were identified, two, Sec16L and GRP78, are associated with the ER. Sec16L (KIAA0310) functions in the export of proteins from the ER [36]. GRP78 is particularly interesting because it is a key regulator of the cellular response to ER stress, as discussed in the introduction.…”
Section: Hsp105 Client Proteinsmentioning
confidence: 99%
“…Elle est soluble et inactive dans le cytoplasme lorsqu'elle est liée à une molécule de GDP (guanosine diphosphate). Lorsque le facteur d'échange Sec12 catalyse la substitution du GDP par un GTP (guanosine triphosphate), il provoque le changement de conformation de Sar1, qui ainsi activée s'attache à la membrane du RE [6] et se positionne dans un site d'export via son interaction avec la protéine Sec16 [7]. Sar1 recrute alors le premier étage du manteau COPII, l'hétérodimère Sec23/Sec24 qui à son tour recrute diverses protéines « passagères » diffusant dans la membrane pour peu qu'elles arborent un motif de reconnaissance spécifique.…”
Section: Comment Fabriquer Une Vésicule : L'exemple Des Vésicules Copiiunclassified